In vivo CYP2E1 phenotyping as a new potential biomarker of occupational and experimental exposure to benzene - Piccoli, P.; Carrieri, M.; Padovano, L.; Di Mare, M.; Bartolucci, G. B.; Fracasso, M. E.; Lepera, José Salvador [UNESP]; Manno, M. (Elsevier B.V., 2010)
Assessing CYP2E1 phenotype in vivo may be important to predict individual susceptibility to those chemicals, including benzene, which are metabolically activated by this isoenzyme. Chlorzoxazone (CHZ), a specific CYP2E1 substrate, is readily hydroxylated to 6-OH-chlorzoxazone (6-OH-CHZ) by liver CYP2E1 and the metabolic ratio 6-OH-CHZ/CHZ in serum (MR) is a specific and sensitive biomarker of CYP2E1 activity in vivo in humans. We used this MR as a potential biomarker of effect in benzene-treated rats and, also, in humans occupationally exposed to low levels of benzene. Male Sprague-Dawley rats (375-400 g b.w.) were treated i.p. for 3 days with either a 0.5 ml solution of benzene (5 mmol/kg b.w.) in corn oil, or 0.5 ml corn oil alone. Twenty-four hours after the last injection, a polyethylene glycol (PEG) solution of CHZ (20 mg/kg b.w.) was injected i.p. in both treated and control animals. After 2, 5.10,15, 20,30,45, 60, 90, 120, 180, and 240 min from injection, 0.2 ml blood was taken from the tip tail and stored at -20 degrees C until analysis. A modified reverse phase HPLC method using a 5 mu m Ultrasphere C18 column equipped with a direct-connection ODS guard column, was used to measure CHZ and its metabolite 6-OH-CHZ in serum. No statistically significant difference in the MR was observed, at any sampling time, between benzene-treated and control rats. The concentration-versus-time area under the curve (AUC), however, was lower (p < 0.05, Mann-Whitney test), whereas the systemic clearance was higher (p < 0.05) in treated than in control rats. Eleven petrochemical workers occupationally exposed to low levels of airborne benzene (mean +/- SD, 25.0 +/- 24.4 mu g/m(3)) and 13 non-exposed controls from the same factory (mean +/- SD, 6.7 +/- 4.0 mu g/m(3)) signed an informed consent form and were administered 500 mg CHZ p.o. Two hours later a venous blood sample was taken for CHZ and 6-OH-CHZ measurements. Despite exposed subjects showed significantly higher levels of t,t-MA and S-PMA, two biomarkers of exposure to benzene, than non-exposed workers, no difference in the MR mean values +/- SD was found between exposed (0.59 +/- 0.29) and non-exposed (0.57 +/- 0.23) subjects. So, benzene was found to modify CHZ disposition, but not CYP2E1 phenotype in benzene-treated rats, nor in workers exposed to benzene, probably due to the levels of exposure being too low. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Benzene; CYP2E1; Chlorzoxazone; 6-OH-chlorzoxazone; Metabolic phenotype